Identifying needs for the mobile data services : a cross-border strategic perspective - Au, Alfred Ko Chin (2008)
This study focuses on Singapore, Hong Kong SAR and China, as viewed from Shenzhen. It focuse s on strategic issues including entry to multiple markets, market segmentation, venture formation and strategic alliances, etc.